Accumulation of F-Spondin in Injured Peripheral Nerve Promotes the Outgrowth of Sensory Axons - Burstyn-Cohen, Tal (J Neurosci, 1998)
F-spondin, an extracellular matrix protein, is present in peripheral nerve during embryonic development, but its amount diminishes by birth. Axotomy of adult rat sciatic nerve, however, causes a massive upregulation of both F-spondin mRNA and protein distal to the lesion. F-spondin in the distal stump of axotomized nerve promotes neurite outgrowth of sensory neurons, as revealed by protein neutralization with F-spondin-specific antibodies. Thus, F-spondin is likely to play a role in promoting axonal regeneration after nerve injury.